Genotypic diversity in willow (Salix spp.) is associated with chemical and morphological polymorphism, suggesting human-assisted dissemination in the Eastern Mediterranean. (August 2020) - Muklada, Hussein; Davidovich-Rikanati, Rachel; Wilkerson, Dustin G.; Klein, Joshua D.; Deutch-Traubman, Tova; Zou, Junzhu; Awabdeh, Sami; Sweidan, Rawad; Landau, Serge Yan; Schwartz, Amnon; Lewinsohn, Efraim; Smart, Lawrence B.
Graphical abstract: Image 1 Highlights: Three major genetically different groups of willow identified in Israel and Jordan. Contrary to previous assumptions, Salix alba is not widespread in this area (1/34 accessions). Strong matching found between genotype and chemotype in willow accessions. Genotype, chemotype and leaf phenotype, are associated with rust susceptibility. Possible human intervention in the dissemination of willow in the Eastern Mediterranean.